Local community acceptance of the rare earth industry: the case of the Lynas Advanced Materials Plant (LAMP) in Malaysia - Tengku Ismail, Tengku Hanidza; Juahir, Hafizan; Aris, Ahmad Zaharin; Md Zain, Sharifuddin; Abu Samah, Mohd Armi (Springer, 2016)
This paper provides a detailed analysis of the local community response to a newly installed rare earth (RE) refinery facility and the factors underlying its acceptance. House-to-house interviews, using structured questionnaire, were conducted in 2013 (N = 370). Results show that the community was divided into deciding whether they agreed with the presence of the facility, 41.36 % (for) and 41.62 % (against). The remaining fraction of the community was undecided, which made up 17.03 % of the total respondents. This paper identifies six significant predictors of risk acceptance: gender, education status, place of residence, Factor 1 (variables—perception of safety, concern on effects, and trust in the operators), Factor 2 (variables—social and individual benefits), and Factor 3 (variables—no confidence in government). This study gives insights on how the public respond to potential hazardous facilities and highlights the need for policy makers to consider public sentiment which can interfere with further expansion of the RE industry.